Boiling Heat Transfer Coefficient and Critical Heat Flux on Conical Cylindrical Copper under Surface Modification - Nashrullah, Muhammad Dimyati; Sanata, Andi; Solahuddin, Imam; Ilminnafik, Nasrul; Pranoto, Indro; Widyaparaga, Adhika (Journal of Mechanical Engineering Science and Technology (JMEST), 2025)
This study examined how surface roughness and nanoceramic coating, influences the boiling heat transfer coefficient (BHTC) and critical heat flux (CHF) of a conical cylindrical copper test specimen. Three test specimens exhibiting surface roughness of 0.22 µm, 0.14 µm, and 0.04 µm were analyzed for comparison. Two additional test specimens were treated with nanoceramic coatings utilizing silicon carbide as the base material: one specimen received a single-layer coating and the second was applied with a double-layer coating. The behavior of the bubbles was closely observed with a high-speed camera to deepen the analysis. The experimental results showed that the test specimen with higher surface roughness exhibited higher BHTC and CHF. The 0.22 µm surface roughness specimen demonstrated a 55.69% greater BHTC than the 0.04 µm surface roughness specimen. In contrast, the 0.04 µm surface roughness specimen had the lowest CHF, 426.09 kW/m². Nanoceramic coating also enhanced the BHTC and CHF. The specimen with a single-layer coating had the highest BHTC, 40.81% higher than the uncoated specimen. The specimen with a double-layer coating showed a 60.12% increase in CHF compared to the specimen with a single-layer coating. The bubble observation results indicated that test specimens with higher BHTC and CHF had more active nucleation sites. The quantity of active nucleation sites plays a vital role in producing a large number of bubbles, enhancing heat transfer, and maintaining the surface temperature.